IMPROVING LEARNING MODEL OF NARRATIVE TEXT MATERIALS TO IMPROVE LEARNING OUTCOME OF STUDENTS OF CLASS X MIPA 2 SMA NEGERI 1 PURI - Lies Muhshonati (Sean Institute, 2022)
Narrative text material in English subjects in class X MIPA 2 SMA Negeri 1 Puri, students have difficulty in completing lessons, learning outcomes are still below the KKM and student activities tend to be passive. Therefore, classroom action research was conducted with the aim of knowing and describing the implementation and improvement of English learning outcomes for narrative text materials by applying the IMPROVE learning model in class X MIPA 2 SMA Negeri 1 Puri in the even semester of the 2017/2018 academic year. The results showed that, learning by applying the IMPROVE learning model to the narrative text material for English lessons can run effectively and efficiently and improve learning outcomes in class X MIPA 2 SMA Negeri 1 Puri Mojokerto. The results obtained in each cycle include an increase in the quality of learning from 2.64 (good) to 3.64 (very good), student activity increased from 84.44% (active) to 93.33% (very active), and complete learning outcomes increased from 72.73%. (unfinished) to 87.88 % (completed).